Naïve Regulatory T Cell Subset Is Altered in X-Linked Agammaglobulinemia - Shelyakin, Pavel V.; Lupyr, Ksenia R.; Egorov, Evgeny S.; Kofiadi, Ilya A.; Staroverov, Dmitriy B.; Kasatskaya, Sofya A.; Kriukova, Valeriia V.; Shagina, Irina A.; Merzlyak, Ekaterina M.; Nakonechnaya, Tatiana O.; Latysheva, Elena A.; Manto, Irina A.; et al. (Frontiers in Immunology, 2021)
The interplay between T- and B-cell compartments during naïve, effector and memory T cell maturation is critical for a balanced immune response. Primary B-cell immunodeficiency arising from X-linked agammaglobulinemia (XLA) offers a model to explore B cell impact on T cell subsets, starting from the thymic selection. Here we investigated characteristics of naïve and effector T cell subsets in XLA patients, revealing prominent alterations in the corresponding T-cell receptor (TCR) repertoires. We observed immunosenescence in terms of decreased diversity of naïve CD4+ and CD8+ TCR repertoires in XLA donors. The most substantial alterations were found within naïve CD4+ subsets, and we have investigated these in greater detail. In particular, increased clonality and convergence, along with shorter CDR3 regions, suggested narrower focused antigen-specific maturation of thymus-derived naïve Treg (CD4+CD45RA+CD27+CD25+) in the absence of B cells - normally presenting diverse self and commensal antigens. The naïve Treg proportion among naïve CD4 T cells was decreased in XLA patients, supporting the concept of impaired thymic naïve Treg selection. Furthermore, the naïve Treg subset showed prominent differences at the transcriptome level, including increased expression of genes specific for antigen-presenting and myeloid cells. Altogether, our findings suggest active B cell involvement in CD4 T cell subsets maturation, including B cell-dependent expansion of the naïve Treg TCR repertoire that enables better control of self-reactive T cells.